Nivel de Satisfacción de la Corporación Nacional de Electricidad Agencia San Juan - Montoya Suarez, Josue Anthony (2018)
The National Electricity Corporation CNEL EP, is an entity intended to provide the public service of distribution and commercialization of electric energy within the geographical area designated as its concession area, guaranteeing current and future consumers, the continuous and efficient supply of all the power and energy required according to the technical parameters and the regulations that regulate the quality regime and provision of services